2014
DOI: 10.1111/jsr.12138
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamo–pituitary–adrenal axis, glucose metabolism and TNFα in narcolepsy

Abstract: SUMMARYNarcolepsy with cataplexy is caused by a deficiency in the production of hypocretin/orexin, which regulates sleep and wakefulness, and also influences appetite, neuroendocrine functions and metabolism. In this case-control study, 11 patients with narcolepsy with cataplexy and 11 healthy adults underwent an oral glucose tolerance test, and dexamethasone suppression/corticotropin-releasing hormone stimulation test. The average age of patients and controls was 35.1 AE 13.2 and 41.0 AE 2.9 years, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Our study indicates that besides hypocretin deficiency, there is also a marked loss of CRH‐positive neurons selectively in the PVN. This may explain earlier findings, such as a 60% reduction in the basal secretion of ACTH in patients with NT1, 19 and lower plasma levels of cortisol after dexamethasone suppression 20 . The unaffected number of AVP neurons in the biological clock may explain the normal circadian rhythm of adrenocorticotropic hormone 19 .…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Our study indicates that besides hypocretin deficiency, there is also a marked loss of CRH‐positive neurons selectively in the PVN. This may explain earlier findings, such as a 60% reduction in the basal secretion of ACTH in patients with NT1, 19 and lower plasma levels of cortisol after dexamethasone suppression 20 . The unaffected number of AVP neurons in the biological clock may explain the normal circadian rhythm of adrenocorticotropic hormone 19 .…”
Section: Discussionmentioning
confidence: 64%
“…This may explain earlier findings, such as a 60% reduction in the basal secretion of ACTH in patients with NT1, 19 and lower plasma levels of cortisol after dexamethasone suppression. 20 The unaffected number of AVP neurons in the biological clock may explain the normal circadian rhythm of adrenocorticotropic hormone. 19 The marked loss of CRH‐positive neurons in the PVN may provide a novel target for diagnostics and therapeutic interventions, and for identifying the target of the presumed auto‐immune cause of narcolepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects suffering from inflammation frequently exhibit tiredness or sleepiness mediated by the increased production of proinflammatory cytokines in the setting of ‘sickness behavior', which resembles depressive symptoms [4,7]. Narcolepsy, a disorder with increased daytime sleepiness, was found to be associated with specific markers of the HLA system and increased production of proinflammatory cytokines [21,42,43]. Cytokines not only influence wakefulness regulation, but their concentrations also change depending on sleep characteristics or following sleep deprivation [44,45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have also revealed that narcolepsy patients have subtly dysregulated cytokine levels in their serum and CSF consistent with markers of microglial reactivity (Okun et al, 2004 ; Dauvilliers et al, 2014 ; Maurovich-Horvat et al, 2014 ; Tanaka et al, 2014 ). Multiple independent studies that include different ethnic populations showed a preponderant increase in IL-6 and TNFα expression in sera or plasma from patients with narcolepsy (Okun et al, 2004 ; Maurovich-Horvat et al, 2014 ; Tanaka et al, 2014 ). Other studies have identified changes in IL-4 (Dauvilliers et al, 2014 ) or IL-8 (Tanaka et al, 2014 ) levels.…”
Section: Introductionmentioning
confidence: 89%